Interactıon of Micro-Nanoplastics and Heavy Metals in Soil Systems: Mechanism and Implication - Ceylan, Eda; Bartan, Dilara Büşra; Öztürk-Ufuk, Irem; Topuz, Emel; Ayral-Cinar, Derya (Springer Nature, 2024)
Various organic and inorganic contaminants have been detected in soil systems among which heavy metals are one of the most studied ones. Additionally, micro-nanoplastics have been introduced as recent contaminant into soil systems by composting, mulching, biosolid applications, waste disposal, surface run-off, and air deposition. While the fate and toxicity of heavy metals in soil systems have been studied thoroughly, further research in the presence of micro-nanoplastics revealed requirement to investigate interaction of micro-nanoplastics and heavy metals in soil systems. Mechanisms such as adsorption, complexation, and biotransformation have been explored to understand the interaction between micro-nanoplastics and heavy metals. Literature about mechanisms and interactions indicates that micro-nanoplastics can play a role as a vector for the fate of heavy metals in soil systems depending on various parameters related with environmental conditions and contaminants. Therefore, heavy metals may behave differently when they co-exist with micro-nanoplastics. In relation to this change in the fate of heavy metals in soil systems, their toxic effects on soil organisms could be altered. In this chapter, physical, chemical, and biological mechanisms that affect the interaction of micro-nanoplastics and heavy metals are presented. Also, environmental implications are discussed within the context of mobility and toxicity. © 2025 Elsevier B.V., All rights reserved.
Keywords: Heavy metals; Interaction mechanisms; Micro-nanoplastics; Mobility; Toxicity